A kind of wear-resistant and anti-aging polyurethane shoe glue and preparation method thereof
Through microwave pretreatment and polymerization reaction of modified nano calcium carbonate with recovered lignin, combined with crosslinking of seaweed polyether polyol and bisaldehyde starch, the problem of insufficient organic impurities and self-repair performance in polyurethane shoe glue is solved, and abrasion-resistant, anti-aging and highly self-repaired polyurethane shoe glue is achieved.
Patent Information
- Application Number
- CN202411044444.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The existing polyurethane shoe glue has problems with organic impurities during the epoxidation modification process, which affects its performance and lacks self-repairing performance.
Weather-resistant and anti-aging polyurethane shoe glue is prepared by microwave-assisted pretreatment by adding polyreaction of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine, and cross-linking of seaweed polyether polyol and bisaldehyde starch.
The wear resistance and anti-aging properties of polyurethane shoe glue are improved, the wear is reduced, the tensile strength changes less after aging and is higher than 10MPa, and a self-repair rate of more than 90%.
Smart Images

Figure GDA0005297940890000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane shoe glue preparation, and in particular to wear-resistant and anti-aging polyurethane shoe glue and a preparation method thereof. Background Art
[0002] Polyurethane shoe glue has the advantages of flexibility, impact resistance, strong initial adhesion, low temperature resistance and water resistance (weather resistance), and is widely used in shoe glue and other fields. In order to improve the production efficiency of shoes, polyurethane shoe glue generally needs to ensure a fast drying speed at room temperature (high solid content and low curing performance).
[0003] At present, there are many studies on bio-based polyurethane adhesives. For example, invention patent CN110343496B discloses an epoxidized lignin-based polyurethane adhesive, which uses lignin as a raw material to prepare a polyurethane adhesive, then uses epichlorohydrin to epoxidize the unreacted hydroxyl groups in the lignin, and finally adds an epoxy curing agent for curing and molding.
[0004] The raw material is lignin, a byproduct of pulping and papermaking or biorefining. The most studied method for extracting alkaline lignin is chemical coagulation, which has the advantages of flexible operation and strong process adaptability. However, the precipitate contains a large amount of organic impurities. In the free state, the organic impurities, on the one hand, have a great damage to the functional groups on the lignin, and on the other hand, react with the modified material, which is not conducive to the epoxidation modification process of lignin. In addition, the self-healing performance of the product also needs to be further improved.
[0005] Based on this, the present invention designs a wear-resistant and anti-aging polyurethane shoe glue and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a wear-resistant and anti-aging polyurethane shoe glue and a preparation method thereof.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A wear-resistant and anti-aging polyurethane shoe glue comprises the following raw materials in parts by weight: 15-22 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate, 61-74 parts of recycled lignin, 32-44 parts of seaweed polyether polyol, 4-8.5 parts of dialdehyde starch, 11-15 parts of diamine, and 11.8-15.5 parts of modified nano calcium carbonate;
[0009] The preparation method of the modified nano-calcium carbonate is as follows: NaOH solution is added to the nano-calcium carbonate, and then NH4F solution is added and stirred continuously, and then washed until there is no fluorine ion, so as to obtain the modified nano-calcium carbonate.
[0010] Furthermore, 15-20w% NaOH solution is added to the nano calcium carbonate, and then 1-2 times the volume of NH4F solution is added and stirred continuously.
[0011] Furthermore, the particle size of the modified nano calcium carbonate is 200-300 nm.
[0012] Furthermore, the diamine is one of polyetheramine D-2000 and polyetheramine T-403, or a combination of both.
[0013] A method for preparing wear-resistant and anti-aging polyurethane shoe glue comprises the following steps:
[0014] 1. Preparation of modified nano calcium carbonate
[0015] Add 15-20w% NaOH solution to nano calcium carbonate, then add 1-2 times the volume of NH4F solution and stir continuously, then wash until there is no fluoride ion, thus obtaining modified nano calcium carbonate;
[0016] 2. Primary microwave pretreatment of recovered lignin
[0017] Recovering lignin and modified nano-calcium carbonate, putting them into a reaction container, and subjecting them to microwave heat treatment at 105-113° C. for 25-32 minutes to obtain a pretreated liquid;
[0018] 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid, reacting at 60-80° C. for 20-30 minutes to obtain a prepolymer;
[0019] 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid, reacting at 65-75° C. for 1-2 hours to obtain a cross-linked product;
[0020] 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product;
[0021] 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0022] Furthermore, in step 4, seaweed polyether polyol is added to the pretreated liquid, mixed evenly, and then dialdehyde starch is added.
[0023] Furthermore, step five is specifically as follows: the prepolymer and the cross-linked product are mixed, and stirred and reacted at 103-115° C. for 35-60 minutes, and the liquid becomes a viscous gel-like product.
[0024] Furthermore, step six is specifically as follows: the viscous gel product is reacted at 105-110° C. for 15-35 minutes under microwave assistance, and then cooled to room temperature to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The invention is based on the prepolymer obtained by polyaddition reaction of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine, and after the lignin is recycled and cross-linked with seaweed polyether polyol, the cross-linked product is modified by the prepolymer to obtain the wear-resistant and anti-aging polyurethane shoe glue.
[0027] In the present invention, nano-calcium carbonate is modified, and the recovered lignin and the modified nano-calcium carbonate are subjected to microwave-assisted pretreatment to obtain a pre-treated liquid. The modified nano-calcium carbonate has a relatively developed pore structure and a large specific surface area, and has a good adsorption and fixation effect on the recovered lignin, reducing the movement of free organic impurities in the recovered lignin, on the one hand reducing the damage to the functional groups on the lignin, and on the other hand reducing the reaction of organic impurities with other functional groups, thereby reducing the modification effect on the lignin. At the same time, the modified nano-calcium carbonate has a large specific surface area and good dispersibility, and has a high adsorption strength for polymer chains, which is beneficial to improving the cross-linking density, anti-aging performance and wear resistance of the product, with a wear loss of ≤0.012, and the tensile strength after aging does not change much and is higher than 10MPa;
[0028] When cracks appear in the present invention, the product can be heated to above 50°C, and fusion diffusion and automatic healing can occur. The self-repair rate in 3 minutes (50°C) can reach more than 90%, the polymer network is rebuilt, and the repair process can be completed quickly. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] 1. Preparation of modified nano calcium carbonate
[0032] Add NaOH solution to nano calcium carbonate, then add NH4F solution and stir continuously, then wash until there is no fluoride ion, thus obtaining modified nano calcium carbonate;
[0033] 2. Primary microwave pretreatment of recovered lignin
[0034] Recovering lignin and modified nano-calcium carbonate, placing them in a reaction vessel, and subjecting them to microwave thermal treatment under microwave assistance to obtain a pretreated liquid;
[0035] 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid to react and obtain a prepolymer;
[0036] 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid to react and obtain a cross-linked product;
[0037] 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product;
[0038] 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0039] Specifically, 15w% NaOH solution is added to nano-calcium carbonate, and then 1 volume of NH4F solution is added and stirred continuously, and then washed until there is no fluorine ion, so as to obtain modified nano-calcium carbonate (300nm); 61 parts of lignin and 11.8 parts of modified nano-calcium carbonate are recycled and put into a reaction container, and microwave heat treatment is performed at 105°C for 32 minutes to obtain a pre-treated liquid; 15 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and 15 parts of diamine (polyetheramine D-2000) are added to the pre-treated liquid. , react at 60°C for 30 minutes to obtain a prepolymer; add 32 parts of seaweed polyether polyol (prepared by the method of CN112778512B) to the pretreated liquid, mix evenly, and then continue to add 8.5 parts of dialdehyde starch, react at 65°C for 2 hours to obtain a cross-linked product; the prepolymer and the cross-linked product are mixed, stirred and reacted at 103°C for 60 minutes, and the liquid becomes a viscous gel product; the viscous gel product is reacted at 105°C for 35 minutes with the assistance of microwaves, and then cooled to room temperature to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0040] The polyurethane shoe glue has a viscosity of 256mpa.s and a peel strength (PU) of 45N / mm after drying. It does not turn white or fall off after being placed in 50°C water for 24 hours, meeting the basic performance requirements of adhesives for shoemaking.
[0041] Example 2
[0042] 1. Preparation of modified nano calcium carbonate
[0043] Add NaOH solution to nano calcium carbonate, then add NH4F solution and stir continuously, then wash until there is no fluoride ion, thus obtaining modified nano calcium carbonate;
[0044] 2. Primary microwave pretreatment of recovered lignin
[0045] Recovering lignin and modified nano-calcium carbonate, placing them in a reaction vessel, and subjecting them to microwave thermal treatment under microwave assistance to obtain a pretreated liquid;
[0046] 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid to react and obtain a prepolymer;
[0047] 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid to react and obtain a cross-linked product;
[0048] 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product;
[0049] 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0050] Specifically, 20w% NaOH solution was added to nano-calcium carbonate, and then 2 times the volume of NH4F solution was added and stirred continuously, and then washed until there was no fluorine ion, so as to obtain modified nano-calcium carbonate (200nm); 74 parts of lignin and 15.5 parts of modified nano-calcium carbonate were recycled and put into a reaction container, and microwave-assisted microwave heat treatment was performed at 113°C for 25 minutes to obtain a pre-treated liquid; 22 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and 11 parts of diamine (polyetheramine T-403) were added to the pre-treated liquid. ), react at 80°C for 20min to obtain a prepolymer; add 44 parts of seaweed polyether polyol (prepared by the method of CN112778512B) to the pretreated liquid, mix evenly, continue to add 4 parts of dialdehyde starch, react at 75°C for 1h to obtain a cross-linked product; the prepolymer and the cross-linked product are mixed, stirred and reacted at 115°C for 35min, and the liquid becomes a viscous gel product; the viscous gel product is reacted at 110°C for 15min with the assistance of microwaves, and then cooled to room temperature to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0051] Example 3
[0052] 1. Preparation of modified nano calcium carbonate
[0053] Add NaOH solution to nano calcium carbonate, then add NH4F solution and stir continuously, then wash until there is no fluoride ion, thus obtaining modified nano calcium carbonate;
[0054] 2. Primary microwave pretreatment of recovered lignin
[0055] Recovering lignin and modified nano-calcium carbonate, placing them in a reaction vessel, and subjecting them to microwave thermal treatment under microwave assistance to obtain a pretreated liquid;
[0056] 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid to react and obtain a prepolymer;
[0057] 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid to react and obtain a cross-linked product;
[0058] 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product;
[0059] 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0060] Specifically, 18w% NaOH solution was added to nano-calcium carbonate, and then 1.6 times the volume of NH4F solution was added and stirred continuously, and then washed until there was no fluorine ion, so as to obtain modified nano-calcium carbonate (250nm); 64 parts of lignin and 13.5 parts of modified nano-calcium carbonate were recycled and put into a reaction container, and microwave-assisted microwave heat treatment was performed at 108°C for 28 minutes to obtain a pre-treated liquid; 19 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and 13 parts of diamine (polyetheramine D-2000: polyetheramine T- 403=1:1), react at 70℃ for 25min to obtain a prepolymer; add 34 parts of seaweed polyether polyol (prepared by the method of CN112778512B) to the pretreated liquid, mix evenly, then continue to add 6 parts of dialdehyde starch, react at 68℃ for 1.3h to obtain a cross-linked product; the prepolymer and the cross-linked product are mixed, stirred and reacted at 105℃ for 45min, and the liquid becomes a viscous gel product; the viscous gel product is reacted at 108℃ for 25min with the assistance of microwaves, and then cooled to room temperature to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0061] Comparative Example 1
[0062] The difference from Example 3 is that the nano calcium carbonate is not modified.
[0063] 1. Take nano calcium carbonate without modification;
[0064] 2. Primary microwave pretreatment of recovered lignin
[0065] Recovering lignin and nano-calcium carbonate, putting them into a reaction container, and subjecting them to microwave thermal treatment under microwave assistance to obtain a pretreated liquid;
[0066] 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid to react and obtain a prepolymer;
[0067] 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid to react and obtain a cross-linked product;
[0068] 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product;
[0069] 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0070] Specifically: 64 parts of recycled lignin and 13.5 parts of nano calcium carbonate are put into a reaction container, and microwave heat treatment is performed at 108°C for 28 minutes under microwave assistance to obtain a pretreated liquid; 19 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and 13 parts of diamine (polyetheramine D-2000: polyetheramine T-403=1:1) are added to the pretreated liquid, and reacted at 70°C for 25 minutes to obtain a prepolymer; 34 parts of seaweed polyether polyol (prepared by the method of CN112778512B) are added to the pretreated liquid, and after mixing evenly, 6 parts of dialdehyde starch are continuously added, and reacted at 68°C for 1.3 hours to obtain a cross-linked product; the prepolymer and the cross-linked product are mixed, and stirred and reacted at 105°C for 45 minutes, and the liquid becomes a viscous gel product; the viscous gel product is reacted at 108°C for 25 minutes under microwave assistance, and then cooled to room temperature to obtain a wear-resistant and anti-aging polyurethane shoe glue.
[0071] Comparative Example 2
[0072] The difference from Example 3 is that the preparation steps of the pretreatment liquid are as follows: 64 parts of recovered lignin and 13.5 parts of modified nano-calcium carbonate are put into a reaction container and mixed to obtain the pretreatment liquid.
[0073] 1. Preparation of modified nano calcium carbonate
[0074] Add NaOH solution to nano calcium carbonate, then add NH4F solution and stir continuously, then wash until there is no fluoride ion, thus obtaining modified nano calcium carbonate;
[0075] 2. Primary microwave pretreatment of recovered lignin
[0076] Recovered lignin and modified nano-calcium carbonate are placed in a reaction container without microwave heat treatment, and mixed to obtain a pre-treated liquid;
[0077] 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid to react and obtain a prepolymer;
[0078] 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid to react and obtain a cross-linked product;
[0079] 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product;
[0080] 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0081] Specifically, 18w% NaOH solution is added to nano-calcium carbonate, and then 1.6 times the volume of NH4F solution is added and stirred continuously, and then washed until there is no fluorine ion, so as to obtain modified nano-calcium carbonate (250nm); 64 parts of lignin and 13.5 parts of modified nano-calcium carbonate are put into a reaction container, and are not subjected to microwave heat treatment, and are mixed uniformly to obtain a pre-treated liquid; 19 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and 13 parts of diamine (polyetheramine D-2000: polyetheramine T-403= 1:1), react at 70°C for 25min to obtain a prepolymer; add 34 parts of seaweed polyether polyol (prepared by the method of CN112778512B) to the pretreated liquid, mix well, continue to add 6 parts of dialdehyde starch, react at 68°C for 1.3h to obtain a cross-linked product; the prepolymer and the cross-linked product are mixed, stirred and reacted at 105°C for 45min, and the liquid becomes a viscous gel product; the viscous gel product is reacted at 108°C for 25min with the assistance of microwaves, and then cooled to room temperature to obtain wear-resistant and anti-aging polyurethane shoe glue.
[0082] Test experiment
[0083] After the polyurethane shoe glues of Examples 1 to 3 and Comparative Examples 1 to 2 were cured, the cured samples were tested for wear resistance, anti-aging, and self-repairing. The results are shown in Table 1 below.
[0084] Wear resistance test: GB / T 1689-2014;
[0085] Aging test: Place the cured samples in a damp heat aging box at a temperature of 80°C and a relative humidity of 90%, keep the sample spacing at 5cm, and conduct an aging test for 18 weeks; perform a tensile test in accordance with GB / T528-2009 at a tensile speed of 500mm / min.
[0086] Self-repairing experiment: The cured samples were treated with the surface scratch method, and the scratch widths before and after 3 min (50 ° C) were counted to calculate the self-repairing rate.
[0087]
[0088] The invention is based on the prepolymer obtained by polyaddition reaction of 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine, and after the lignin is recycled and cross-linked with seaweed polyether polyol, the cross-linked product is modified by the prepolymer to obtain the wear-resistant and anti-aging polyurethane shoe glue.
[0089] In the present invention, nano-calcium carbonate is modified, and the recovered lignin and the modified nano-calcium carbonate are subjected to microwave-assisted pretreatment to obtain a pre-treated liquid. The modified nano-calcium carbonate has a relatively developed pore structure and a large specific surface area, and has a good adsorption and fixation effect on the recovered lignin, reducing the movement of free organic impurities in the recovered lignin, on the one hand reducing the damage to the functional groups on the lignin, and on the other hand reducing the reaction of organic impurities with other functional groups, thereby reducing the modification effect on the lignin. At the same time, the modified nano-calcium carbonate has a large specific surface area and good dispersibility, and has a high adsorption strength for polymer chains, which is beneficial to improving the cross-linking density, anti-aging performance and wear resistance of the product, with a wear loss of ≤0.012, and the tensile strength after aging does not change much and is higher than 10MPa;
[0090] When cracks appear in the present invention, the product can be heated to above 50°C, and fusion diffusion and automatic healing can occur. The self-repair rate in 3 minutes (50°C) can reach more than 90%, the polymer network is rebuilt, and the repair process can be completed quickly.
[0091] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A wear-resistant and anti-aging polyurethane shoe glue, characterized in that: The method comprises the following raw materials in parts by weight: 15 to 22 parts of 2-ethoxycarbonyl-2-methyltrimethylene carbonate, 61 to 74 parts of recovered lignin, 32 to 44 parts of seaweed polyether polyol, 4 to 8.5 parts of dialdehyde starch, 11 to 15 parts of diamine, and 11.8 to 15.5 parts of modified nano calcium carbonate; The preparation method of the modified nano-calcium carbonate is as follows: NaOH solution is added to the nano-calcium carbonate, and then NH4F solution is added and stirred continuously, and then washed until there is no fluoride ion, so as to obtain the modified nano-calcium carbonate; The recovered lignin and modified nano-calcium carbonate are put into a reaction container and subjected to microwave heat treatment under microwave assistance to obtain a pre-treated liquid for preparing wear-resistant and anti-aging polyurethane shoe glue; the microwave heat treatment has a temperature of 105-113° C. and a treatment time of 25-32 minutes.
2. The wear-resistant and anti-aging polyurethane shoe glue according to claim 1, characterized in that: 15-20w% NaOH solution is added to nano calcium carbonate, and then 1-2 times the volume of NH4F solution is added and stirred continuously.
3. The wear-resistant and anti-aging polyurethane shoe glue according to claim 2, characterized in that: The particle size of the modified nano calcium carbonate is 200-300 nm.
4. The wear-resistant and anti-aging polyurethane shoe glue according to claim 3, characterized in that: The diamine is polyetheramine D-2000.
5. A method for preparing the wear-resistant and anti-aging polyurethane shoe glue according to claim 4, characterized in that: The following steps are involved:
1. Preparation of modified nano calcium carbonate Add NaOH solution to nano calcium carbonate, then add 1 to 2 times the volume of NH4F solution and stir continuously, then wash until there is no fluoride ion, thus obtaining modified nano calcium carbonate; 2. Primary microwave pretreatment of recovered lignin Recovering lignin and modified nano-calcium carbonate, placing them in a reaction vessel, and subjecting them to microwave thermal treatment under microwave assistance to obtain a pretreated liquid; 3. Adding 2-ethoxycarbonyl-2-methyltrimethylene carbonate and diamine to the pretreated liquid, reacting at 60-80° C. for 20-30 minutes to obtain a prepolymer; 4. adding seaweed polyether polyol and dialdehyde starch to the pretreatment liquid, reacting at 65-75° C. for 1-2 hours to obtain a cross-linked product; 5. Mix the prepolymer and the cross-linked product, and stir until the liquid turns into a viscous gel-like product; 6. The viscous gel product is subjected to secondary microwave treatment to obtain wear-resistant and anti-aging polyurethane shoe glue.
6. The method for preparing the wear-resistant and anti-aging polyurethane shoe glue according to claim 5, characterized in that: The concentration of the NaOH solution in step 1 is 15-20w%.
7. The method for preparing the wear-resistant and anti-aging polyurethane shoe glue according to claim 5, characterized in that: The microwave heat treatment in step 2 has a temperature of 105-113° C. and a treatment time of 25-32 min.
8. The method for preparing the wear-resistant and anti-aging polyurethane shoe glue according to claim 5, characterized in that: In step 4, seaweed polyether polyol is added to the pretreated liquid, mixed evenly, and then dialdehyde starch is added.
9. The method for preparing the wear-resistant and anti-aging polyurethane shoe glue according to claim 6, characterized in that: Step five is as follows: the prepolymer and the cross-linked product are mixed, and stirred at 103-115° C. for 35-60 minutes, and the liquid becomes a viscous gel-like product.
10. The method for preparing the wear-resistant and anti-aging polyurethane shoe glue according to claim 7, characterized in that In, Step six is as follows: the viscous gel product is reacted at 105-110°C for 15-35 minutes under microwave assistance. After that, the temperature is cooled to room temperature to obtain wear-resistant and anti-aging polyurethane shoe glue.
Citation Information
Patent Citations
An epoxidized lignin-based polyurethane adhesive
CN110343496B
Biomass-based polyether polyols made from seaweed and their preparation methods
CN112778512B
Non-isocyanate polyurethane adhesive capable of being adhered in situ for long time in severe environment and preparation method of non-isocyanate polyurethane adhesive
CN117070179A